2022
DOI: 10.1098/rspb.2021.2682
|View full text |Cite
|
Sign up to set email alerts
|

The roles of growth regulation and appendage patterning genes in the morphogenesis of treehopper pronota

Abstract: Treehoppers of the insect family Membracidae have evolved enlarged and elaborate pronotal structures, which is hypothesized to involve co-opted expression of genes that are shared with the wings. Here, we investigate the similarity between the pronotum and wings in relation to growth. Our study reveals that the ontogenetic allometry of the pronotum is similar to that of wings in Membracidae, but not the outgroup. Using transcriptomics, we identify genes related to translation and protein synthesis, which are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…These hypotheses illustrate how simple pairwise comparisons of structures will often be inadequate to resolve serial homology relationships or determine whether the concept of serial homology is applicable. For example, to determine whether treehopper helmets are novel or serially homologous to wings (Kudla et al, 2022;Prud'homme et al, 2011), these structures must be compared at the appropriate organizational level and, if they are homologous, assessed for whether their homology is embedded in an evolutionary character tree or paramorph hierarchy. It is possible that helmets are serially homologous to wings because they belong to an exite-derived character family, or the character family of some other basal F I G U R E 4 A basal wingless insect from the suborder Monura (order Archaeognatha), illustrating proposed source tissues for wing origins.…”
Section: Insect Wing Serial Homologsmentioning
confidence: 99%
“…These hypotheses illustrate how simple pairwise comparisons of structures will often be inadequate to resolve serial homology relationships or determine whether the concept of serial homology is applicable. For example, to determine whether treehopper helmets are novel or serially homologous to wings (Kudla et al, 2022;Prud'homme et al, 2011), these structures must be compared at the appropriate organizational level and, if they are homologous, assessed for whether their homology is embedded in an evolutionary character tree or paramorph hierarchy. It is possible that helmets are serially homologous to wings because they belong to an exite-derived character family, or the character family of some other basal F I G U R E 4 A basal wingless insect from the suborder Monura (order Archaeognatha), illustrating proposed source tissues for wing origins.…”
Section: Insect Wing Serial Homologsmentioning
confidence: 99%
“…This focus stems from the dramatic change in size that occurs between these two stages when the pronotum takes on the adult morphology. We found, however, that shapes characteristics of the adult form are already visible in earlier instars (Figure 2) (Kudla et al, 2022). This indicates that patterning of many aspects of adult pronotal morphology develops gradually and progressively during the nymphal instars.…”
Section: Introductionmentioning
confidence: 70%
“…The Hippo pathway is linked to the Insulin/mTOR signaling by way of the transcription factor Yorkie (McKenna et al, 2019;Straßburger et al, 2012). In our previous work we showed that the fifth instar pronotum overexpressed many genes related to protein synthesis, cell growth, and cell proliferation linked to the eIF2 pathway and the mTOR and eIF4/ p70S6K pathways (Kudla et al, 2022), The spatial positioning of signaling molecules in the anterior region could allow for greater cell proliferation along the anterior median carina than anywhere else, leading to a raised bump in the subsequent nymphal stage that eventually becomes an anterior horn. Each nymphal instar represents a distinct developmental timepoint with quantifiable changes in shape, and the mechanisms of species-specific spatial patterning of differential growth could be uncovered by comparative molecular studies of early instars.…”
Section: Possible Mechanisms Behind the Membracid Menageriementioning
confidence: 99%
See 1 more Smart Citation